EOQ model for non-instantaneous deteriorating items with time-varying demand and partial backlogging. (2nd March 2009) - Manna, S.K.; Lee, C.C.; Chiang, C.
In this study, an EOQ model is developed for non-instantaneous deteriorating items with demand rate as time-dependent. In the model, shortages are allowed and partially backlogged. The backlogging rate is variable and dependent on the waiting time for the next replenishment. Analytical results indicate that the optimal re-order time of the proposed model is unique and independent of the form of demand rate. Results are illustrated with the help of numerical examples. Computational results show that a decrease in the backlogging parameter causes the lower average total cost per unit time.